Analisis Efisiensi Kinerja Motor BLDC Menggunakan Metode Kontrol Sliding Mode Observer PI - Adi Mulyadi; Muhammad Zainal Rois; Bambang Sri Kaloko; Riska Fita Lestari; R. B. Moch. Gozali; Suprihadi Prasetyono (Jurnal Arus Elektro Indonesia, 2022)
Brushless DC (BLDC) motors are widely used and applied in industry but it is difficult to control BLDC motors. Basically, a Brusless DC (BLDC) motor or also known as a permanent magnet synchronous motor (PMSM) uses a hall sensor to determine the position and speed of the motor. The data on the value of the BLDC rotor speed (rpm) in the basic modeling of the BLDC motor as input from the sliding mode observer (SMO) method which is set in the BLDC rotor speed (rpm) set point. A sensorless method based on SMO is proposed to replace the hall-sensor device for estimating the rotor position and speed of BLDC motors. This study compares the value between the rotor speed (rpm) of BLDC without control and the rotor speed (rpm) of BLDC with control. PI control is one that determines the rotor speed efficiency of the BLDC. The most optimal value of Rotor Rotation Efficiency (rpm) using PI Control is at the rotor rotation speed of 2000 rpm and 2500 rpm or 100%. The value of Rotor Rotation efficiency (rpm) is greater, namely 100% or 2000 rpm from the 2000 rpm rotation speed set point for BLDC motor modeling using PI control when compared to BLDC motor modeling without PI control, namely 91.65% or 1833 rmp value from set point rotation speed 2500 rpm.